Pengaruh Kebijakan Utang Terhadap Nilai Perusahaan pada Perusahaan Terdaftar Indeks LQ45 tahun 2024 - Aini, Latifah Nazwa; Saputri, Tia Nanda; Rizky, Nanda Fathiya; Antika, Neta (Journal of Accounting Law Communication and Technology, 2025)
This study aims to evaluate the effect of debt policy on firm value in companies listed in the LQ45 Index on the Indonesia Stock Exchange (IDX) in 2024. The research uses quantitative methods with secondary data obtained from the company's annual report and financial statements for the period 2022-2024. Data analysis was carried out using multiple linear regression models on E-Views 12 software. The results showed that debt policy has a positive and significant effect on firm value, while capital structure has no significant effect. The findings provide insights for financial managers and investors in designing optimal financial policies to increase firm value.